2022
DOI: 10.2174/1872210515666210329161439
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of α-Pinene Loaded Self-emulsifying Nanoformulation for In-Vivo Anti-Parkinson's Activity

Abstract: Aim: The aim of the present study was to develop and optimize the self-nanoemulsifying drug delivery system of α-pinene (ALP-SNEDDS) and to evaluate its in-vivo anti-Parkinson’s activity. Background: Different lipid-based drug delivery technologies have been researched to upgrade the bioavailability of such drug candidates and to expand their clinical adequacy upon oral administration. Self-emulsifying drug delivery system (SEDDS) have pulled in expanding interests and, specifically, self-nanoemulsifying d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A small number of SEDDS-based products have already been successfully introduced into the pharmaceutical market, with none of them loading drugs for the treatment of neurological disorders. Until now, several in vivo assays using oral SEDDS have been carried out for neuropharmaceuticals brain targeting [ 4 , 6 , 23 , 24 , 25 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 70 ], but only a few in vivo pre-clinical studies have been reported for IN administration of neurotherapeutics loaded in SEDDS. In fact, only six studies were found that investigated the IN administration of neurotherapeutics loaded in SEDDS: clonazepam [ 45 ], diazepam [ 44 ], and perampanel [ 28 ] for epilepsy treatment; Bdph for glioblastoma treatment [ 4 ]; huperzine A [ 30 ] for Alzheimer’s disease; and naringin [ 5 ] as a neuroprotective for Alzheimer’s and Parkinson’s disease.…”
Section: Application Of Sedds In Brain Drug Delivery—pre-clinical Stu...mentioning
confidence: 99%
See 3 more Smart Citations
“…A small number of SEDDS-based products have already been successfully introduced into the pharmaceutical market, with none of them loading drugs for the treatment of neurological disorders. Until now, several in vivo assays using oral SEDDS have been carried out for neuropharmaceuticals brain targeting [ 4 , 6 , 23 , 24 , 25 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 70 ], but only a few in vivo pre-clinical studies have been reported for IN administration of neurotherapeutics loaded in SEDDS. In fact, only six studies were found that investigated the IN administration of neurotherapeutics loaded in SEDDS: clonazepam [ 45 ], diazepam [ 44 ], and perampanel [ 28 ] for epilepsy treatment; Bdph for glioblastoma treatment [ 4 ]; huperzine A [ 30 ] for Alzheimer’s disease; and naringin [ 5 ] as a neuroprotective for Alzheimer’s and Parkinson’s disease.…”
Section: Application Of Sedds In Brain Drug Delivery—pre-clinical Stu...mentioning
confidence: 99%
“…This demonstrates the advantages of using nasal SEDDS rather than a simple nasal solution, the oral route or the invasive IV route for brain delivery of drugs. By analyzing Table 2 , it is noted that, despite the pharmacokinetic evaluation, some authors also performed behavioral studies to compare the efficacy and safety of drugs loaded in SEDDS administered with those of simple solutions, suspensions or commercial preparations of the same drugs [ 4 , 25 , 29 , 31 , 32 , 33 , 46 , 48 , 49 , 50 ]. For the case of glioblastoma treatment, efficacy was directly assessed after oral administration of chlorogenic acid SMEDDS [ 48 ] or the new prodrug 13a-(S)-3-pivaloylocyl-6,7-dimethoxyphenanthro(9,10-b)-indolizidine (CAT3) [ 49 ].…”
Section: Application Of Sedds In Brain Drug Delivery—pre-clinical Stu...mentioning
confidence: 99%
See 2 more Smart Citations
“…Data were analyzed using one-way and two-way analysis of variance followed by and Transcutol-HP (20%) as a drug, carrier oil, surfactant, and cosurfactant, respectively. [40] The formulation was further subjected to in vitro and in vivo safety and efficacy assessment.…”
Section: Complete Resistancementioning
confidence: 99%